Motivasi dan Kesejahteraan Karyawan: Pilar Perubahan yang Berkelanjutan - Mukrodi Mukrodi; Agratha Friezsanda (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Sustainable organizational change has become a critical challenge in the context of rapid technological advancement, increasing work demands, and evolving employee expectations. Many organizations continue to prioritize short-term performance targets while underestimating the strategic role of employee motivation and well-being, which may undermine long-term organizational sustainability. This study aims to examine how employee motivation and well-being function as fundamental pillars in supporting sustainable organizational change. Using a descriptive qualitative approach, this research is based on a structured literature review of recent national and international academic publications relevant to motivation, employee well-being, human resource management, and organizational sustainability. The analysis synthesizes key concepts and empirical findings to identify patterns and relationships among the studied variables. The results indicate that employees with high motivation and adequate well-being covering physical, psychological, social, and economic dimensions demonstrate higher productivity, stronger organizational commitment, greater loyalty, and improved adaptability to organizational change. Furthermore, employee well-being serves as a foundational condition that enables motivational strategies to operate effectively over time. This study highlights the importance of integrating motivation and holistic well-being into human resource management strategies to support sustainable organizational transformation. The findings contribute to theoretical discussions on sustainable human resource management and offer practical insights for organizations seeking long-term stability and competitiveness.